Sintered body and method for producing the same
Patent Information
- Application Number
- JP2023122686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-27
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-07-27
AI Technical Summary
【0017】 具現例に係る石英ガラスベースの焼結体は、従来の合成石英ガラスと比較して向上したプラズマ耐食性を有することができる。
Smart Images

Figure 0007637727000006 
Figure 0007637727000007 
Figure 0007637727000008
Abstract
Description
[Technical field]
[0001] The embodiments relate to a sintered body containing silicon oxide and partially containing carbon, and a method for manufacturing the sintered body. [Background technology]
[0002] The plasma processing method used as a dry etching method, which is one of the semiconductor manufacturing processes, is a method of etching a target object using fluorine-based gases, etc. Recently, in the manufacture of electronic devices, designs have become increasingly finer, and in particular, higher dimensional accuracy is required in plasma processing, and high power is used.
[0003] Such plasma processing apparatuses may contain quartz glass components that are affected by plasma. Quartz glass generates relatively few impurities, so it is possible to prevent contamination of the etching target. Various studies have been conducted to extend the life of such quartz glass-related components in plasma processing apparatuses, and it is necessary to consider a method for improving the limitations of quartz glass to improve the life and durability of the components.
[0004] The above-mentioned background art is technical information that the inventor possessed for the purpose of deriving the embodiments or that he / she acquired in the process of deriving the embodiments, and is not necessarily publicly known art that was disclosed to the general public prior to the filing of the application of the present invention.
[0005] Related prior art includes "Method for manufacturing synthetic quartz" disclosed in Korean Patent Registration No. 10-2388688 and "SiO2 molded body, its manufacturing method and use" disclosed in Korean Patent Publication No. 10-2006-0057618. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the embodiment is to provide a quartz glass-based sintered body exhibiting excellent plasma resistance properties and a method for manufacturing the same. [Means for solving the problem]
[0007] In order to achieve the above object, the sintered body according to the embodiment is Contains silicon oxide and carbon, In the Raman spectrum, 1311 cm -1 ~1371cm -1 The D band peak at 1572 cm -1 ~1632cm -1 It has a G-band peak at a wave number of The D band peak or the G band peak is at 1027 cm -1 ~1087cm -1 The fifth peak may have an intensity greater than that of the fifth peak present at a wavenumber of 100 .mu.m.
[0008] In one embodiment, the D band peak or the G band peak is at 762 cm -1 ~822cm -1 The fourth peak may have an intensity greater than that of the fourth peak present at a wavenumber of 100 .mu.m.
[0009] In one embodiment, the Raman spectrum shows -1 ~1262cm -1 The average intensity of this wavenumber may be greater than the intensity of the fifth peak.
[0010] In an embodiment, the ratio Id / Ig of the intensity of the D band peak to the G band peak may be 0.9 to 1.5.
[0011] In an embodiment, the sintered body may have a compressive strength of 380 MPa to 580 MPa.
[0012] In one embodiment, the carbon content may be from 0.01% to 1.5% by weight based on the total weight.
[0013] In one embodiment, the sintered body has a thickness reduction rate of 1.38% or less after etching under plasma etching conditions in a chamber compared to before etching; The plasma etching conditions may be as follows: chamber pressure 100 mTorr, plasma power 800 W, exposure time 300 minutes, CF4 flow rate 50 sccm, Ar flow rate 100 sccm, O2 flow rate 20 sccm.
[0014] In order to achieve the above object, a method for producing a sintered body according to an embodiment includes the steps of: A granulation step of forming the raw material composition into a granule form; and a sintering step of molding, carbonizing and sintering the raw material composition in the form of granules. The raw material composition may include silicon oxide, a carbonizing resin, and auxiliary additives.
[0015] In an embodiment, the content of the carbonization resin may be 0.1% by weight to 8% by weight based on the total weight of the raw material composition.
[0016] In one embodiment, the granulation step comprises: The raw material composition may be spray-dried. Effect of the Invention
[0017] The quartz glass-based sintered body according to the embodiment may have improved plasma corrosion resistance compared to conventional synthetic quartz glass. [Brief description of the drawings]
[0018] [Figure 1] 1 is a graph of Raman spectra showing intensity according to wavenumber by Raman spectroscopy in Example 1 (E1) and Comparative Examples 1 and 2 (CE1 and CE2) performed in experimental examples. [Diagram 2] 1 shows sample photographs of Example 1 (E1) and Comparative Examples 1 and 2 (CE1 and CE2). [Diagram 3]1 is a graph showing the results of an F1s scan in an XPS analysis of Example 1 (E1) and Comparative Examples 1 and 2 (CE1 and CE2) performed in experimental examples. BEST MODE FOR CARRYING OUT THEINVENTION
[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS One or more exemplary embodiments will now be described in detail with reference to the accompanying drawings in order to enable those of ordinary skill in the art to easily make and use the present invention. However, the exemplary embodiments may be embodied in many different forms and are not limited to the embodiments set forth herein. Like reference numerals are used throughout the specification to refer to like parts.
[0020] In this specification, when a certain configuration "includes" another configuration, this does not mean to exclude the other configurations, unless specifically stated to the contrary, but rather means that the other configurations may also be included.
[0021] In this specification, when a certain component is said to be "connected" to another component, this includes not only the case where the component is "directly connected" but also the case where the component is "connected via another component between them."
[0022] In this specification, the term "B is located on A" means that B is located on A in direct contact therewith, or that B is located on A with another layer located therebetween, and is not to be interpreted as being limited to B being located in contact with the surface of A.
[0023] As used herein, the term "combinations thereof" contained in a Markush form expression means a mixture or combination of one or more selected from the group of components set forth in the Markush form expression, and is meant to include one or more selected from the group of components.
[0024] In this specification, the phrase "A and / or B" means "A, B, or A and B."
[0025] In this specification, terms such as "first", "second" or "A", "B" are used to distinguish identical terms from each other, unless otherwise specified.
[0026] In this specification, the term "singular" is to be construed as including the singular or plural as the context requires, unless otherwise specified.
[0027] Sintered body In order to achieve the above object, the sintered body according to the embodiment is Contains silicon oxide and carbon, In the Raman spectrum obtained through Raman spectroscopy, -1 ~1371cm -1 The D band peak at 1572 cm -1 ~1632cm -1 It has a G-band peak at a wave number of The D band peak and / or the G band peak are at 1027 cm in the Raman spectrum. -1 ~1087cm -1 The fifth peak may have an intensity greater than that of the fifth peak present at a wavenumber of 100 .mu.m.
[0028] Silica glass is a type of glass made of silicon oxide (SiO2) and is an important material in semiconductor processing due to its low thermal expansion coefficient and chemical durability.
[0029] In an embodiment, a quartz glass sintered body is invented in which a certain carbon can be applied as a type of defect in the Si-O amorphous network structure, and the quartz glass sintered body can have Raman spectrum, chromaticity, transmittance, reflectance, plasma etching resistance, compressive strength, etc. different from conventional quartz glass.
[0030] The Raman spectrum of the sintered body can be obtained using a Raman spectrometer DxR2 manufactured by Thermo Scientific, and the specific conditions will be described later in the following experimental examples.
[0031] The Raman spectrum of the general quartz glass (CE1, CE2) and the Raman spectrum of the sintered body of the embodiment (E1) are compared in Figure 1. It can be seen from this that the Raman spectrum of the general quartz glass and the sintered body of the embodiment have a common Si-O related peak.
[0032] Specifically, 421cm -1 ~441cm -1 The first peak, 478 cm, is associated with the vibration of SiO2. -1 ~498cm -1 A second peak at 582 cm is associated with the breathing vibration of oxygen atoms in the four-membered and three-membered rings. -1 ~622cm -1 A third peak at 762 cm, which is associated with the breathing vibration of the oxygen atom in the three-membered ring, exists at a wavenumber of -1 ~822cm -1 A fourth peak, at 1027 cm, which is associated with bending of the Si-O-Si bridges -1 ~1087cm -1 A fifth peak, which is associated with Si-O stretching and exists at a wavenumber of 100 Hz, can be seen.
[0033] The sintered body of the embodiment has a lower intensity of the fifth peak and a peak intensity of 1057 cm compared to general synthetic quartz glass. -1 It can be seen that the trends are different at wavenumbers above 1192 cm. -1 However, it can be seen that in the embodiment, a clear peak does not appear in this region due to the influence of defective carbon. It can be seen that the sintered body of the embodiment has a structural difference that can improve the plasma etching resistance.
[0034] In the Raman spectrum of the sintered body, the D band peak or the G band peak is at 1027 cm -1 ~1087cm -1The D band peak or the G band peak may have an intensity 1.5 times or more, 2 times or more, or 5 times or less than the intensity of the fifth peak. The sintered body exhibiting such a Raman spectrum can exhibit further improved plasma etching resistance due to defective carbon.
[0035] In the Raman spectrum of the sintered body, the D band peak or the G band peak is at 762 cm -1 ~822cm -1 The D band peak or the G band peak may have an intensity greater than that of the fourth peak at a wave number of 1.2 times or more, 1.5 times or more, or 4 times or less than that of the fourth peak. The sintered body exhibiting such a Raman spectrum can exhibit further improved plasma etching resistance due to defective carbon.
[0036] In the Raman spectrum of the sintered body, the ratio Id / Ig of the intensity of the D band peak to the G band peak may be 0.9 or more and may be 1.5 or less. In the sintered body exhibiting such a Raman spectrum, defective carbon may be metastably located in the network structure of Si-O.
[0037] The intensity of the fifth peak in the Raman spectrum of the sintered body may be greater than the intensity of the fifth peak of synthetic quartz glass and commercial quartz glass (NIFS-S product of NIKON and N product of TOSOH). -1 ~1700cm -1 The integral of the intensity over wavenumber is 600cm -1 ~1100cm -1 The sintered body exhibiting such a Raman spectrum can exhibit further improved plasma etching resistance due to its unique structure.
[0038] The Raman spectrum of the sintered body shows a value of 1212 cm -1 ~1262cm -1 The average intensity of the wave number is 1027 cm -1 ~1087cm -1 The intensity of the fifth peak at a wave number of 1000 to 15000 can be greater than the intensity of the fifth peak at a wave number of 1000 to 15000. The sintered body exhibiting such a Raman spectrum can exhibit further improved plasma etching resistance due to its unique structure.
[0039] The sintered body may have an amorphous structure that is substantially free of long-range order and has some short-range order.
[0040] The sintered body can form a stable polymer layer by partial reaction of the carbon on the surface of the sintered body with an etching gas such as CF4, thereby further improving the plasma etching resistance.
[0041] The sintered body may have a compressive strength of 380 MPa or more and 580 MPa or less, or 400 MPa or more and 550 MPa or less. The sintered body having such compressive strength can be stably positioned in a plasma etching device.
[0042] The carbon content of the sintered body may be 0.01% to 1.5% by weight, 0.2% to 1.3% by weight, or 0.3% to 1% by weight. By having such a carbon content, it can be appropriately distributed within the structure of the amorphous quartz glass, and plasma corrosion resistance can be ensured.
[0043] The sintered body may contain impurities other than the silicon oxide and carbon.
[0044] The silicon oxide of the sintered body can be close to SiO2, which is the silicon oxide component of the raw material.
[0045] The silicon content of the sintered body may be 40% by weight or more and 49% by weight or less.
[0046] The oxygen content of the sintered body may be 47% by weight or more and 56% by weight or less.
[0047] The sintered body may have a thickness reduction rate of 1.38% or less, or 1.35% or less, after etching under plasma etching conditions in a chamber, compared to before etching. The thickness reduction rate can be calculated as follows.
[0048] [Formula 1] Thickness reduction rate % = {(thickness before etching - thickness after etching) / thickness before etching} x 100%
[0049] The plasma etching conditions may be as follows: chamber pressure 100 mTorr, plasma power 800 W, exposure time 300 minutes, CF4 flow rate 50 sccm, Ar flow rate 100 sccm, O2 flow rate 20 sccm.
[0050] The sintered body has such a thickness reduction rate (etching rate) and thus can exhibit improved plasma etching resistance compared to conventional quartz glass.
[0051] The sintered body may have a weight loss rate of 1.4% or less, or 1.38% or less, after etching under the plasma etching conditions as compared to before etching. The weight loss rate can be calculated as follows.
[0052] [Formula 2] Weight reduction rate % = {(weight before etching - weight after etching) / weight before etching} x 100%
[0053] By having such a weight reduction rate, the sintered body can exhibit improved plasma etching resistance compared to conventional quartz glass.
[0054] The sintered body may have a lower fluorine content generated after etching under the above plasma etching conditions than synthetic quartz glass.
[0055] The sintered body may have a lower carbon reduction amount after etching under the above plasma etching conditions than synthetic quartz glass.
[0056] The sintered body has a resistivity of 4.1×10 at 25° C. 15 Ωcm or more, or 4.4×10 15 The sintered body may have a resistivity of 6.0×10 Ωcm or more at 25° C. 15 It may be less than 5.8×10 Ωcm or 15 It may be Ωcm or less.
[0057] The sintered body may have an L* value in the CIE L*a*b* color space in accordance with ASTM E1164 of 0 or more, 10 or more, or 15 or more. The L* value may be 85 or less, 60 or less, or 35 or less.
[0058] The sintered body may have an a* value in the CIE L*a*b* color space in accordance with ASTM E1164 of 1 or more, or may be 2 or more. The a* value may be 8 or less, or may be 5 or less.
[0059] The sintered body may have a b* value in the CIE L*a*b* color space according to ASTM E1164 of 2 or more, or may be 5 or more. The b* value may be 20 or less, or may be 15 or less.
[0060] The range of L*, a*, and b* values of the sintered body is considered to be due to the influence of defective carbon, and in particular, there is a clear difference in L* value compared to general quartz glass, and it can have a dark color and black color. The sintered body having such a range of L*, a*, and b* values can be expected to have further improved plasma corrosion resistance.
[0061] The CIE L*a*b* color space values of the sintered body can be measured by the method described in the following experimental examples.
[0062] The sintered body may have a reflectance of 1% or more, or 2% or more, with respect to light having a wavelength of 550 nm. The reflectance may be 8% or less, or 6.5% or less.
[0063] The sintered body may have a transmittance of 0.5% or more, or 1% or more, for light with a wavelength of 550 nm, and the transmittance may be 30% or less, or 10% or less.
[0064] The reflectance and transmittance of the sintered body are considered to be due to the influence of defective carbon, and in particular, there is a clear difference in light transmittance compared to general quartz glass, and the transmittance is even lower. The sintered body having such optical properties is expected to have further improved plasma corrosion resistance.
[0065] The optical properties such as reflectance and transmittance of the sintered body can be measured by the methods described in the following Experimental Examples.
[0066] The purity of the sintered body may be 99% by weight or more, or 99.99% by weight or more, based on carbon, silicon, and oxygen. The purity may be 99.9999% by weight or less.
[0067] The sintered body may contain small amounts of metallic impurities such as magnesium, potassium, calcium, chromium, iron, nickel, and barium, in addition to carbon.
[0068] The magnesium content of the sintered body may be 100 ppb or more and 2500 ppb or less based on the total weight.
[0069] The potassium content of the sintered body may be 500 ppb or more and 2500 ppb or less based on the total weight.
[0070] The calcium content of the sintered body may be 1000 ppb or more and 12000 ppb or less based on the total weight.
[0071] The chromium content of the sintered body may be 100 ppb or more and 1000 ppb or less based on the total weight.
[0072] The iron content of the sintered body may be 800 ppb or more and 5000 ppb or less based on the total weight.
[0073] The nickel content of the sintered body may be 50 ppb or more and 800 ppb or less based on the total weight.
[0074] The barium content of the sintered body may be 100 ppb or more and 2000 ppb or less based on the total weight.
[0075] The sintered body is in harmony with such predetermined metallic impurities, and is expected to have good durability.
[0076] Plasma etching resistant parts In order to achieve the above object, the plasma etching resistant part according to the embodiment may include the sintered body. Exemplarily, the sintered body may be included in the entire area of the plasma etching resistant part, or may be included as a coating layer of a predetermined thickness on the surface of the plasma etching resistant part. The thickness of the coating layer may be adjusted in consideration of the degree of plasma etching, and may be 50 mm or more and 1000 mm or less.
[0077] The plasma etching resistant part may be, for example, a focus ring, but may also correspond to other parts that are affected by plasma etching in a plasma etching apparatus.
[0078] Manufacturing method of sintered body In order to achieve the above object, a method for producing a sintered body according to an embodiment includes: A granulation step of forming the raw material composition into a granule form; and a sintering step of molding, carbonizing and sintering the raw material composition in the form of granules. The raw material composition may include silicon oxide, a carbonizing resin, and auxiliary additives.
[0079] The granulation step is a step of forming a slurry of a raw material composition including silicon oxide, a carbonization resin, an auxiliary additive, a solvent, etc. into a granule form of a predetermined particle size. Through the granulation step, the sinterability of the next step can be improved, and the raw material components can be distributed more uniformly.
[0080] The granulation step may be performed by spray drying the raw material composition. For example, a slurry of the raw material composition including a solvent may be atomized through a spray nozzle, and the gas-liquid mixture and the solvent may be evaporated to form dried granules.
[0081] The particle size of the raw material granules obtained in the granulation step may be 5 μm or more and 95 μm or less.
[0082] The silicon oxide (SiO2) in the raw material composition may be in powder form.
[0083] The carbonization resin of the raw material composition may include polyvinyl alcohol (PVA)-based resin, phenol-based resin, polyvinyl butyral (PVB), etc., and may illustratively include polyvinyl alcohol-based resin.
[0084] The auxiliary additives of the raw material composition may include polyacrylic acid-based resins, polycarboxylic acid-based resins, C10-C40 alkanes (paraffins), fatty acid amides, etc. The auxiliary additives may act as binders, dispersants, etc.
[0085] The solvent for the raw material composition may include an alcohol-based solvent, water, or the like.
[0086] The content of the polymer resin for carbonization may be 0.1% by weight to 8% by weight, or 0.3% by weight to 6% by weight, based on the total raw material composition. By having such a content, defective carbon can be appropriately distributed in the structure of the amorphous quartz glass of the sintered body manufactured through the subsequent process, and plasma corrosion resistance can be improved.
[0087] The content of the auxiliary additive may be 1% by weight or more and 8% by weight or less, or may be 2% by weight to 6% by weight, based on the total weight of the raw material composition.
[0088] The shaping of the sintering step may be carried out by injecting the raw material composition in the form of granules into a mold containing the shape of the desired part.
[0089] The carbonization in the sintering step may be carried out by heat treatment at a temperature of 700° C. or more and 1100° C. or less.
[0090] The sintering step may be performed by heat treatment at a temperature of 1100° C. to 1300° C. for 1 hour to 10 hours.
[0091] The sintered body obtained through the sintering step may have the above-mentioned characteristics.
[0092] The present invention will be described in more detail with reference to the following specific examples. The following examples are merely illustrative for the purpose of aiding understanding of the present invention, and are not intended to limit the scope of the present invention.
[0093] Example 1 - Production of quartz glass sintered body containing defective carbon A raw material composition was prepared by mixing 95% by weight of silicon oxide powder from Sukgyung AT, 1% by weight of PVA205 polyvinyl alcohol resin and PVA217 polyvinyl alcohol resin from Kuraraya as carbonization resins (PVA205:PVA217 mixed at a weight ratio of 19.6:80.4), 4% by weight of substances including Celuna D-305, Celuna P-222, Hymicron L-271, and HS551 as auxiliary additives, and the remaining amount of solvent, and was spray-dried to form granules with a particle size of about 40 to 60 μm. The granules were injected into a focus ring mold to form a sintered body by sintering at a temperature of 1260 °C for 6 hours.
[0094] Comparative Example 1 - Synthesized quartz glass The microscope is equipped with NIFS-S quartz glass made by Nikon with a purity of 99.9%.
[0095] Comparative Example 2 - Quartz glass produced by fusion method The device was equipped with 99.9% pure quartz glass N manufactured by TOSOH.
[0096] Experimental example - Raman analysis The sintered body of Example 1 and the quartz glass of the comparative example were subjected to Raman spectroscopy under the following measurement conditions using a Raman spectrometer LabRam Aramis manufactured by Horiba Jobin Yvon, and the Raman spectra are shown in FIG. Excitation wavelength: 514 nm, output: 5 mW, resolution: 1.5 cm -1 , Scan range: 1×1μm, Measurement time: 300 seconds
[0097] Referring to FIG. 1, the sintered body of Example 1 (E1) and the quartz glasses of Comparative Examples 1 and 2 (CE1 and CE2) all have a common peak related to amorphous SiO (431 cm -1 , 488cm -1 , 602cm -1 , 792cm -1 , 1057cm -1 ) was shown, but 1057 cm -1The difference can be seen at wave numbers exceeding 1341 cm in the case of Example 1. -1 , 1602cm -1 In the comparative example, no such peaks appeared even though the comparative example contained a portion of carbon.
[0098] Experimental example - Measurement of chromaticity, transmittance and reflectance The chromaticity and reflectance of the sintered body of Example 1 and the quartz glass of the comparative example were measured under the following conditions using a KONICA MINOLTA CM-5 instrument in accordance with ASTM E1164, and sample photographs were taken. The results are shown in FIG. 2 and Table 1. Light source: Xenon lamp (D65), viewing angle: 10°, wavelength interval: 10nm, wavelength range: 360~740nm
[0099] The transmittance of the sintered body of Example 1 and the quartz glass of the Comparative Example was measured under the following conditions using a V-730 instrument manufactured by JASCO Corporation. The results are shown in Table 1. Wavelength range: 200~1100nm, scanning speed: 400nm / min
[0100] [Table 1]
[0101] Referring to Table 1, it can be seen that in the case of Example 1, due to the influence of defective carbon, the L* value in the CIE L*a*b* color space and the transmittance are significantly lower than those of the comparative example, and as shown in FIG. 2, it can be seen that the sample of the sintered body (E1) of Example 1 is relatively blackish.
[0102] Experimental example - Measurement of plasma corrosion resistance The plasma corrosion resistance of the sintered body of Example 1 and the quartz glass of the comparative example was measured under the following conditions. The results are shown in Table 2. Chamber pressure: 100 mTorr, plasma power: 800 W, exposure time: 300 min, CF4 gas flow rate: 50 sccm, Ar gas flow rate: 100 sccm, O2 gas flow rate: 20 sccm
[0103] [Table 2]
[0104] Referring to Table 2, it was confirmed that the sintered body of Example 1 had a lower thickness reduction rate and weight reduction rate than the quartz glass of the comparative example, and thus had excellent plasma etching resistance.
[0105] Experimental example - XPS analysis before and after plasma etching Before and after the measurement of the plasma corrosion resistance of the sintered body of Example 1 and the quartz glass of the Comparative Example, X-ray photoelectron spectroscopy (XPS) was performed using a Sigma Probe device manufactured by Thermo VG Scientific. The results are shown in FIG.
[0106] [Table 3]
[0107] Referring to FIG. 3 and Table 3, it can be seen that the sintered body of Example 1 has a relatively small change in carbon before and after plasma etching compared to the quartz glass of the comparative example, and the amount of F generated by reaction with the etching gas is also low.
[0108] Experimental example - XRF and ICP-MS analysis The X-ray fluorescence spectroscopy (XRF) of the sintered body of Example 1 and the quartz glass of the comparative example was analyzed using a ZSX Primus instrument manufactured by Rigaku, and the impurity content was measured using an inductively coupled plasma mass spectrometry (ICP-MS) using an HR-ICP / MS instrument manufactured by Thermo Fisher Scientific. The results are shown in Tables 4 and 5, respectively.
[0109] [Table 4]
[0110] Referring to Table 4, it can be confirmed by XRF analysis that the sintered body of Example 1 and the quartz glass of the comparative example both have similar carbon, oxygen, and silicon contents.
[0111] [Table 5]
[0112] Referring to Table 5, the results of ICP-MS show that the sintered body of Example 1 has higher contents of magnesium, potassium, calcium, chromium, iron, nickel, and barium than the comparative example.
[0113] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the appended claims also fall within the scope of the present invention.
Claims
1. Contains silicon oxide and carbon, In the Raman spectrum, 1311 cm -1 ~1371cm -1 and the D band peak at 1572 cm -1 ~1632cm -1 has a G-band peak at a wave number of The D band peak or the G band peak is at 1027 cm -1 ~1087cm -1 The sintered body has an intensity greater than the fifth peak present at a wave number of 1000.
2. The D band peak or the G band peak is at 762 cm -1 ~822cm -1 The sintered body according to claim 1, having an intensity greater than a fourth peak present at a wave number of 1000.
3. In the Raman spectrum, -1 ~1262cm -1 The sintered body according to claim 1 , wherein the average intensity of the wavenumber of the fifth peak is greater than the intensity of the fifth peak.
4. 2. The sintered body according to claim 1, wherein the ratio Id / Ig of the intensities of the D band peak and the G band peak is 0.9 or more and 1.5 or less.
5. 2. The sintered body according to claim 1, wherein the carbon content is from 0.01% by weight to 1.5% by weight based on the total weight.
6. The reduction in thickness after etching under the plasma etching conditions in the chamber is 1.38% or less compared to before etching; The plasma etching conditions were: chamber pressure 100 mTorr, plasma power 800 W, exposure time 300 minutes, CF 4 The flow rate of Ar was 50 sccm, the flow rate of O was 100 sccm, 2 2. The sintered body according to claim 1, wherein the flow rate of is 20 sccm.
7. The sintered body according to claim 1, having an L* value in the CIE L*a*b* color space in accordance with ASTM E1164 of 0 to 85.
8. A method for producing the sintered body according to claim 1, comprising the steps of: A granulation step of forming the raw material composition into a granule form; and a sintering step of molding, carbonizing and sintering the raw material composition in the form of granules. The raw material composition comprises silicon oxide, a carbonizing resin and an auxiliary additive.
9. The method according to claim 8 , wherein the content of the resin for carbonization is 0.1% by weight or more and 8% by weight or less with respect to the entire raw material composition.
10. The auxiliary additive is The method according to claim 8, comprising one selected from the group consisting of polyacrylic acid-based resins, polycarboxylic acid-based resins, C10-C40 alkanes, fatty acid amides, and combinations thereof.
Citation Information
Patent Citations
Black silicon dioxide-based corrosion resistant member and its production
JP2000281430A
Sintered quartz and its production
JP2001058870A